Mixed Codes in Mindy Cake & Cookies Recipe Book by Mindy Mot - Kusumaningrum, Ni Ketut Veri (LPPM Undiksha, 2020)
This study aims to find out understanding and analyzing the forms of code mixing, the types and factors of code mixing happened in this book was written by Mindy Mot. The technique of data collection used literate study. The method of this research used descriptive qualitative method. The object of this research is â€œThe Mindy Cake & Cookiesâ€ as a recipe book written by Mindy Mot. The result showed that there were words and phrases form of code mixing in the recipe book â€œMindy Cake & Cookiesâ€ by Mindy Mot. The type of code mixing in this book was named as code mixing out. In this book, there was no mixed code found because Mindy Mot did not insert the regional languages in her book. The writing of the recipe book used Indonesian which was inserted into English therefore it was found an only code mixing out. The factors caused the mixing of codes in â€œMindy Cake & Cookiesâ€ recipe book by Mindy Mot are the perception of the authorâ€™s language background, language dominance, language attitude, psycholinguistic motivation, commercialization for the target market.Â